Sensitization of T cells to CD95-mediated apoptosis by HIV-1 Tat and gp120 - Westendorp, Michael; Frank, Rainer; Ochsenbauer, Christina; Stricker, Kirstin; Dhein, Jens; Walczak, Henning; Debatin, Klaus-Michael; Krammer, Peter H. (Nature, 1995)
THE depletion of CD4+ T cells in AIDS is correlated with high turnover of the human immunodeficiency virus HIV-1,2 and associated with apoptosis3-5. The molecular mechanism of apoptosis in HIV infection, however, is largely unknown. T-cell apoptosis might be affected by viral proteins such as HIV-1 Tat6-9 and gp120 (refs 10, 11). T-cell-receptor (TCR)-induced apoptosis was recently shown to involve the CD95 (APO-1/Fas) receptor12. We show here that HIV-1 Tat strongly sensitizes TCR- and CD4(gpl20)-induced apoptosis by upregulation of CD95 ligand expression. Concentrations of Tat found to be effective in cultures of HIV-1-infected cells were also observed in sera from HIV-1-infected individuals. Taken together, our results indicate that HIV-1 Tat and gp!20 accelerate CD95-mediated, activation-induced T-cell apoptosis, a mechanism that may contribute to CD4+T-cell depletion5,13,14 in AIDS.
Gesehen am 17.09.2024